(untitled) (Journal of Information Technology and Digital World, 2025)
Effective inventory management is the secret to success in the current high-speed marketing world. Traditional remote inventory management relies on image processing to identify missing products from shelves but mainly contributes to customer privacy concerns. Unlike previous work that focused on identifying missing specific items, this work aims to identify empty areas on shelves without infringing customer identity. In addition to capturing the exact position of empty shelves in a store, it also captures the regions of empty shelves. On top of this, the system has a function that can also detect low levels of inventory and identify the specific items that require replenishment. This is achieved by leveraging top-end technologies such as Optical Character Recognition (OCR) for labeling products, convolutional neural networks (CNNs) to detect stock levels, and a database-driven stock management system to track in real-time and analyze inventories. The system incorporates the pre-trained Faster R-CNN model currently in use for detecting vacant shelves and a hybrid OCR-CNN model to spot item labels and quantities. The system has a replenishment module for creating monthly reports that aggregate shelf occupancy information, low-stock instances, and replenishment activities. The informative reports provide actionable data, trend analysis, and performance metrics, which can be easily presented to management to drive strategic planning. This breakthrough solution offers a privacy-centric, all-in-one approach to shelf monitoring, low stock detection, inventory replenishment, and performance reporting, addressing pressing requirements in the retail sector.